Pertumbuhan Stek Pucuk Mangga (Mangifera indica L.) terhadap Respon Konsentrasi IBA (Indole Butyric Acid) dan Macam Media Tanam: Growth of Mango Shoot Cuttings (Mangifera indica L.) on the Response of IBA (Indole Butyric Acid) Concentrations and Types of Planting Media - Zainol Arifin Zainol Arifin; Ida Sugeng Suyani; Aprilia Hartanti (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2023)
Mango (Mangifera indica L.) is a fruit plant that has long been known and has become a commodity that has high economic value and is a trade commodity between countries. Vegetative propagation technique is an alternative to reproduce this type of plant. This study aims to: 1) Determine the concentration of IBA (Indole Butyric Acid) which affects the growth of mango shoot cuttings (Mangifera indica L.). 2) Knowing the planting media that affect the growth of mango shoot cuttings (Mangifera indica L.). 3) To determine the interaction between the concentration of IBA (Indole Butyric Acid) and the planting medium which influences the growth of mango shoot cuttings (Mangifera indica L.). The research was carried out using Factorial Randomized Block Design (RBD) with 2 factors. The first factor was the concentration of IBA (Indole Butyric Acid) (0 ppm, 500 ppm and 1000 ppm) and the second factor was the planting medium (sand, husk charcoal and sand + husk charcoal) with 3 replications. The results of this study were 1) There was an effect of IBA (Indole Butyric Acid) concentration treatment on the growth of mango shoot cuttings (Mangifera indica L.). The effect occurred on the percentage of growing cuttings, days of shoot break, shoot length, and number of leaves. 2) There is an effect of growing media treatment on the growth of mango shoot cuttings (Mangifera indica L.). The effect occurred on the percentage of growing cuttings, shoot length and number of leaves. 3) There was no interaction between the treatment of IBA (Indole Butyric Acid) concentrations and the growing media on the growth of mango shoot cuttings (Mangifera indica L.).